(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Careful control of indoor wireless coverage is crucial to ensure better signal reception at user-end, mitigate interference to other adjacent wireless systems plus reduce possibility of signal reception by unintended users. Existing solutions are either costly or difficult to configure. This paper presents empirical IEEE802.11 indoor coverage and Transmission Control Protocol (TCP) throughput analysis for WLAN Access Point with corner reflector. The integration of two corner reflector configurations to Access Point was shown to successfully weaken signals by up to 19 dB and 100% of TCP throughput while strengthening signals by up to 6 dB and 40% of TCP throughput for respective intended regions. The results demonstrate potential application of corner reflector to customize indoor coverage and regulate reliable internet connectivity of Access Point.